2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--19744
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Engineering Challenges into Capstone Design and Senior Project Courses

Abstract: The Engineering & Design Department of Eastern Washington University (EWU) recently added a Mechanical Engineering (ME) degree to the existing Mechanical Engineering Technology (MET) program. The ME program is more theoretical and requires more advanced mathematics where the MET program is more hands-on with mathematics requirements up to Calculus II. However, the programs are taught side-by-side and complement each other. When we developed the ME program we wanted to maintain as much of the strong hands-on as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The enthusiasm of the two groups of students allowed us to do a pilot run for a two quarter Capstone course before we could make the official change. In addition, our previous experience has shown that when working with industry-sponsored projects over one quarter there are many additional challenges including not having enough time for shipping parts or obtaining technical assistance 2,11 . Switching to two quarters will permit enough time to obtain the necessary parts and support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enthusiasm of the two groups of students allowed us to do a pilot run for a two quarter Capstone course before we could make the official change. In addition, our previous experience has shown that when working with industry-sponsored projects over one quarter there are many additional challenges including not having enough time for shipping parts or obtaining technical assistance 2,11 . Switching to two quarters will permit enough time to obtain the necessary parts and support.…”
Section: Discussionmentioning
confidence: 99%
“…The same was done after the creation of the ME program and in addition the students were encouraged to seek industry sponsored projects. While some projects were successful, others were not as much 2 . The main challenge encountered was the lack of time, ten weeks seems to be short especially when one takes into account the response time from the company or sponsor and the time needed to ship or obtain necessary parts or services.…”
Section: Introductionmentioning
confidence: 99%